Microwave absorbing characteristics of Fe3O4@SiO2 core–shell polyaniline-based composites. (15th April 2021) - Yusmaniar; Erdawati; Sosiati, Harini; Budi, Setia; Alaydrus, Mudrik; Handoko, Erfan
Abstract: In this study, Fe3 O4 @SiO2 core–shell/polyaniline composites were successfully prepared by mechanical and chemical methods. The crystalline structure, morphology, magnetic and microwave absorption property of the Fe3 O4 @SiO2 core–shell polyaniline-based composites were investigated with X-ray diffraction, scanning electron microscope, permagraph and vector network analyzer, respectively. The results indicate the composites of 4 wt% Fe3 O4 @SiO2 core–shell filleras a potential candidate for X-band electromagnetic absorbing material. The frequency bands for reflection loss below –10 dB (90% microwave absorption) areobtained from 8.0 to 12.2 GHz at the thickness of 2 to 5 mm. This enhancement could be attributed to the addition of Fe3 O4 @SiO2 core–shell as a filler.